1964
DOI: 10.1051/forest/19640301
|View full text |Cite
|
Sign up to set email alerts
|

Application de la Technique de Culture des Tissus Végétaux à l'étude de quelques problèmes de la physiologie de l'arbre

Abstract: Article disponible sur le site http://www.afs-journal.org ou http://dx.doi.org/10.1051/forest/19640301 2" Tissus sans cohésion 400 3" Evolution de la structure 401 4" Tubes criblés 401 C) Réserves 401 D) Lignification 402 Interprétation îles résultats 403Analyse des facteurs agissant sur la différenciation .. 403 -Annulation de la pression radiale 4042 -Maintien de la pression radiale, le cambium étant séparé de la cime 405 3 -Maintien de la pression radiale, le cambium étant séparé à la fois de la cime et de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

1972
1972
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…As with cuttings, the rooting of air-layers is affected by season (65) and is most successful when using seedling tissues (~ fastigata, ~ botyroides, ~ bicostata, ~ saligna) (106) or epicormic shoots (~camaldulensis (75) and E. grandis (71». Adult trees can be layered by grafting adult scions onto seedling rootstocks and applying layers to the scion (71).…”
Section: Air Layeringmentioning
confidence: 99%
See 2 more Smart Citations
“…As with cuttings, the rooting of air-layers is affected by season (65) and is most successful when using seedling tissues (~ fastigata, ~ botyroides, ~ bicostata, ~ saligna) (106) or epicormic shoots (~camaldulensis (75) and E. grandis (71». Adult trees can be layered by grafting adult scions onto seedling rootstocks and applying layers to the scion (71).…”
Section: Air Layeringmentioning
confidence: 99%
“…In early studies (75,115), coconut milk was found to be essential in the culture medium to sustain growth of Eucalyptus callus. However, it was shown (39) that coconut milk was not necessary and that ~ bancroftii callus can grow vigorously on a completely defined medium and ~ grandis, ~ laevopinea, E. melliodora and E. nicholli on a medium with casein hydrolysate.…”
Section: Tissue Culturementioning
confidence: 99%
See 1 more Smart Citation
“…1), ou d'un billon dépourvu de rameaux feuilles et placé dans l'eau) ont montré que la structure de ces tissus est identique dans les trois cas (5).…”
unclassified
“…Ces résultats conduisaient à envisager l'hypothèse de l'existence de facteurs d'organisation provenant des bourgeons ou des pousses et indispensables à la formation de tissus ligneux normaux Certaines expériences de greffes de bourgeons sur un tissu en culture ont effectivement permis d'obtenir la réapparition de cellules lignifiées normales (2,4,5,7). Il s'agissait alors de bourgeons de a même espèce végétale.…”
unclassified